Emergency Department Observation Units and the Older Patient - Moseley, Mark G. (2013)
An increasing number of emergency departments (EDs) are providing extended care and monitoring of patients in ED observation units (EDOUs). EDOUs can be particularly useful for older adults both as an alternative to hospitalization in appropriately selected patients and as a means to risk-stratify older adults with unclear presentations. They can also provide a period of therapeutic intervention and reassessment for older patients in whom the appropriateness and safety of immediate outpatient care is unclear. They offer the opportunity for more comprehensive evaluation of many characteristics of particular importance to the care of older adults which cannot be accomplished during a short ED stay. The manuscript first discusses the general characteristics of EDOUs. Next, it reviews appropriate entry and exclusion criteria for older adults in EDOU including specific focus on several of the most common observation unit protocols, focusing on their relevance to older adults. Finally, it briefly discusses regulatory implications of observation status for patients with Medicare.